DEVELOPMENT OF ACTIVE LEARNING IN ACCOUNTING STUDENT AT VOCATIONAL SCHOOL MEDIATED BY LEARNING MOTIVATION - Pinkan, Friska Nabilla; Mardi; Susanti, Santi (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This study aims to determine the effect of learning styles and learning readiness on learning activeness which is mediated by learning motivation in students of financial and institutional accounting expertise programs at State Vocational Schools in the city and district of Bogor. In this study, quantitative and survey methodologies were utilized. The reachable population in this study amounted to 139 respondents majoring in Financial and Institutional Accounting of X1 grade at SMK Negeri 1 Bogor and SMK Negeri 2 Cibinong. The sample used was 103 respondents using a proportional random sampling technique. Data collection techniques using a questionnaire instrument. The data analysis technique used to test the hypothesis is by using path analysis and Sobel test. The results of this study revealed that learning styles have a positive but not significant effect on learning activity. Readiness to learn has a positive and significant effect on active learning. Learning styles have a positive and significant influence on learning motivation. Readiness to learn has a positive and significant influence on learning motivation. Motivation to learn has a positive and significant influence on active learning. Learning styles have a direct and indirect effect on learning activity through the mediation of learning motivation. Learning readiness has a direct and indirect effect on active learning through the mediation of learning motivation. Overall, this study explains that the active learning of students at State Vocational High Schools can be created and developed through appropriate learning styles and a good level of learning readiness.